2017
DOI: 10.1016/j.ajog.2017.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of prophylactic salpingectomy during vaginal hysterectomy

Abstract: BACKGROUND: The American Congress of Obstetricians and Gynecologists recommends that “the surgeon and patient discuss the potential benefits of the removal of the fallopian tubes during a hysterectomy in women at population risk of ovarian cancer who are not having an oophorectomy,” resulting in an increasing rate of salpingectomy at the time of hysterectomy. Rates of salpingectomy are highest for laparoscopic and lowest for vaginal hysterectomy. OBJECTIVE: The primary objective of this study was to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 17 publications
(16 reference statements)
1
22
2
Order By: Relevance
“…Therefore, a tailored approach to OS during this type of surgery is comprehensible. Previous research demonstrated OS to be feasible in 81%–88% of vaginal hysterectomies [1225]. However, respondents in our cohort estimated OS to be feasible in approximately half of the cases.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Therefore, a tailored approach to OS during this type of surgery is comprehensible. Previous research demonstrated OS to be feasible in 81%–88% of vaginal hysterectomies [1225]. However, respondents in our cohort estimated OS to be feasible in approximately half of the cases.…”
Section: Discussioncontrasting
confidence: 60%
“…Several studies investigated this issue, with no difference in ovarian reserve after salpingectomy [789]. Furthermore, there is no evidence for an increased complication rate after OS [68] and literature on surgical time suggests a minor increase of 0–13 minutes, depending on surgical approach [8101112].…”
Section: Introductionmentioning
confidence: 99%
“…In another study evaluating salpingo-oophorectomy by the transvaginal route, 127 patients (109 patients with concurrent VH and 18 patients with previous VH) had transvaginal salpingo-oophorectomy, and it was found that complications developed in 9 of the 109 patients (fever, bleeding, ureteral injury, return to operating theatre) [15]. In a multi-centre prospective study evaluating 69 patients who underwent bilateral salpingectomy during VH, Antosh et al [16] reported that mean operating time for bilateral salpingectomy was 11 minutes (± 5.6), with additional estimated blood loss of 6 mL (± 16.3). There were eight surgical complications, none of which was due to the salpingectomy.…”
Section: Discussionmentioning
confidence: 99%
“…stated that PBS increases operating time by 11 min and blood loss by 6 ml. [ 17 ] However, it did not increase the complication rate of surgeries. [ 18 ] In Italia, PBS is already well-known among the Italian OBGYNs as the attempt to reduce ovarian cancer incidence.…”
Section: Discussionmentioning
confidence: 99%